2022
DOI: 10.1007/s00068-022-02017-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum sclerostin levels in osteoporotic fracture patients

Abstract: Purpose Sclerostin inhibits bone formation and stimulates bone resorption. Previous studies found a positive association between bone density and serum sclerostin, but literature on sclerostin levels in osteoporotic fracture patients is scarce. The aim of the present study was to compare the serum sclerostin levels in osteoporotic and non-osteoporotic fracture patients and to assess the correlation of the sclerostin levels with bone mineral density and vitamin D status. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Sclerostin is predominantly synthesized by osteocytes; a possible explanation of the lower levels of sclerostin in osteoporotic patients is the age-dependent reduction in osteocyte number/density and change in morphology. This alteration might result in a decreased functioning of the osteocyte, including the production of sclerostin [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sclerostin is predominantly synthesized by osteocytes; a possible explanation of the lower levels of sclerostin in osteoporotic patients is the age-dependent reduction in osteocyte number/density and change in morphology. This alteration might result in a decreased functioning of the osteocyte, including the production of sclerostin [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, postmenopausal women demonstrate increased sclerostin levels [ 59 ]. Although it might be expected that sclerostin and Dkk1 are inversely correlated with BMD in postmenopausal women, several studies have revealeda positive association between BMD and sclerostin and Dkk1 [ 60 , 61 , 62 ]. For instance, a recent study found a positive correlation between sclerostin and Dkk1 expression in bone from postmenopausal women with osteoporosis and BMD, with their serum levels reflecting their bone levels [ 60 ].…”
Section: Novel Bone Markersmentioning
confidence: 99%

Novel Biomarkers of Bone Metabolism

Fernández-Villabrille,
Martín-Carro,
Martín-Vírgala
et al. 2024
Nutrients
“…Recently, many studies have been conducted on the role of sclerostin and Wnt signaling in the treatment of osteoporosis [17,18]. However, there are still many uncertainties about the effect of sclerostin, and in particular, there are not many studies on the correlation between sclerostin and risedronate, including bisphosphonates.…”
Section: Introductionmentioning
confidence: 99%